Directions for expanding the potential of using human capital in the post-war reconstruction of the Ukrainian economy. - Hishchak, Bohdan (Ways to Improve Construction Efficiency, 2024)
The article analyzes the directions for expanding the potential use of human capital in the context of Ukraine’s post-war economic recovery. The relevance of the study is driven by the significant reduction in the working-age population, which has decreased by 40% compared to the pre-war period, as well as the urgent need to develop and implement effective state strategies to stabilize the labor market and ensure sustainable economic growth. The study examines modern scientific approaches to assessing the role of human capital in economic growth and identifies key factors for its restoration and expansion. The article outlines the current challenges Ukraine faces in human capital development, including the significant destruction of educational and medical infrastructure, mass population migration, job losses, and declining education levels. As a result, workforce qualifications have deteriorated, and a portion of the population has been forced to seek employment abroad. The negative impact of these factors on the country’s economic potential necessitates the immediate implementation of reforms and innovative approaches in education, employment, and social policy. Special attention is given to the analysis of state programs for retraining and upskilling the workforce, initiatives supporting the employment of socially vulnerable groups, and the development of digital tools in education and the labor market. Measures to stimulate entrepreneurial activity, reintegrate internally displaced persons, and encourage employers to create new jobs are also examined separately. The importance of a comprehensive approach to human capital development is substantiated, emphasizing not only quantitative recovery but also qualitative improvement of labor resources through the enhancement of educational policies, implementation of innovative technologies, and promotion of social integration for various population groups. The article highlights the strategic priorities of state policy in forming a resilient and competitive human capital base as a key factor in Ukraine’s post-war economic revival.